Effect of Stunting Prevention Health Counseling Using Animated Videos on the Knowledge of Brides-to-Be - Ardhi Wiratama Putra; Dian Utama Pratiwi Putri; Noviansyah Noviansyah (Knowledge Dynamics, 2025)
Background: In Indonesia, the prevalence of stunting remains a pressing issue, with rates still considerably high and far from achieving the national target of 14%. One of the critical strategies in addressing this problem is providing adequate education and information to brides-to-be (Catin) regarding pregnancy planning and childcare as a preventive measure against stunting. This study aims to analyze the impact of stunting prevention health counseling using animated video media on improving the knowledge of brides-to-be. Methods: The study involved 60 brides-to-be attending counseling sessions at the BKKBN KB Counseling Center in Rajabasa District, South Lampung Regency. A pre-test and post-test design was utilized to measure changes in knowledge levels. Results: The results showed that prior to the intervention, 25 participants (41.7%) demonstrated good knowledge about stunting prevention. Following the counseling sessions, this number increased significantly to 58 participants (96.7%). Statistical analysis revealed a p-value of 0.0001 (p < 0.05), confirming a significant effect of the intervention. Conclusions: The study highlights the effectiveness of animated video media in delivering health education due to its ability to present information in an engaging, visual, and emotional format. This approach not only enhances comprehension but also sustains interest, making it a valuable tool for increasing awareness and knowledge about stunting prevention among brides-to-be. Strengthening such initiatives can contribute significantly to achieving the national stunting reduction target in Indonesia.